CAUSES OF HEARING DEFECTS AND DESCRIPTION - Turgunbayeva daughter of Zulkhumor Ibrahimjon (Galaxy International Interdisciplinary Research Journal, 2023)
This article describes the causes of deafness and hearing loss, as well as the opinions of foreign scientists.